Game Lino dalam Pembelajaran Bahasa Inggris Materi Many Things Kelas VII Sekolah Menengah Pertama - Nora Maita Sari; Lidya Indah Putri (Universitas Negeri Padang, 2022)
English is an international language where many countries use English in their daily life, such as in Malaysia. English with